The relationship between constructivist approach and inclusive education in primary school - Çibukçiu, Blerina (Frontiers in Education, 2025)
This study aims to present the relationship of the constructivist approach to help inclusive education in primary school and specify which aspects of the constructivist learning environment are related to inclusive education. This research employs a quantitative approach to examine the constructivist approach implementation in inclusive classrooms. Moreover, it is mainly focused on the students and their teachers of the primary schools of Vushtrri, Kosovo. The utilization of a sampling purposive technique has made it possible to select 10 teachers and their classes, while targeting children with specific needs in order to examine the role of constructivist methods in these inclusive environments. Collecting the data was done through two main instruments: The Constructivist Learning Environment Survey (CLES), which is adapted to measure teachers’ perceptions of their teaching environment classroom, and the Teaching Primary Classroom Observation Tool: Strengthening Its Focus on Inclusion to observe structural aspects influencing classroom inclusiveness. This study highlights the importance of constructivist learning environments in fostering inclusive education in primary school. The results show a positive relationship between Personal Relevance and Classroom Culture, Critical Voice and Instruction, Student Negotiation and Socioemotional Skills. These findings suggest that enhancing the learning environment, especially when it is oriented towards a constructivist approach, can result in better inclusive education in primary school. Moreover, these findings help teachers and policymakers to apply constructivist learning environments to encourage Inclusive Education in Primary School.